Adjustment of measurement errors to reconcile precipitation distribution in the high‐altitude Indus basin. (11th April 2018) - Dahri, Zakir Hussain; Moors, Eddy; Ludwig, Fulco; Ahmad, Shakil; Khan, Asif; Ali, Irfan; Kabat, Pavel
Abstract : Precipitation in the high‐altitude Indus basin governs its renewable water resources affecting water, energy and food securities. However, reliable estimates of precipitation climatology and associated hydrological implications are seriously constrained by the quality of observed data. As such, quantitative and spatio‐temporal distributions of precipitation estimated by previous studies in the study area are highly contrasting and uncertain. Generally, scarcity and biased distribution of observed data at the higher altitudes and measurement errors in precipitation observations are the primary causes of such uncertainties. In this study, we integrated precipitation data of 307 observatories with the net snow accumulations estimated through mass balance studies at 21 major glacier zones. Precipitation observations are adjusted for measurement errors using the guidelines and standard methods developed under the WMO's international precipitation measurement intercomparisons, while net snow accumulations are adjusted for ablation losses using standard ablation gradients. The results showed more significant increases in precipitation of individual stations located at higher altitudes during winter months, which are consistent with previous studies. Spatial interpolation of unadjusted precipitation observations and net snow accumulations at monthly scale indicated significant improvements in the quantitative and spatio‐temporal distribution of precipitation over the unadjusted case and previous studies. Adjustment of river flows revealed only a marginal contribution of net glacier mass balance to river flows. The adjusted precipitation estimates are more consistent with the corresponding adjusted river flows. The study recognized that the higher river flows than the corresponding precipitation estimates by the previous studies are mainly due to underestimated precipitation. The results can be useful for water balance studies and bias correction of gridded precipitation products for the study area. Abstract : This study integrated precipitation data of 307 observatories with the net snow accumulations at 21 glaciers and adjusted them for measurement errors and ablation losses. The adjustments revealed average precipitation increase of 21.3% at the basin level, which ranged from 6 to 77% at sub‐basin scale with highest increases at higher altitudes during winter months. The contribution of net glacier mass balance to river flows is only marginal. Data quality‐driven underestimated precipitation is well‐recognized. Figure shows estimated biases from precipitation gauges due to measurement errors and spatial distribution of error‐adjusted annual precipitation.